Direct Saccharification and Fermentation for High Glucose and Ethanol Production from Non‐Detoxified Furfural Residue Without Any Pretreatment. Issue 27 (16th July 2019) - Shi, Xinxin; Zhao, Baofu; Zhou, Haifeng; Tian, Yuanyu; Qiao, Yingyun; Ji, Bei
Abstract: Furfural residue (FR) is utilized directly for bioethanol production without any pretreatment and detoxification. With only 10 FPU g −1 cellulase loading, the glucose yield of FR reached 86.4, 84.6 and 80.5% at solid loadings of 2, 10 and 20%, respectively. When FR is directly used for fermentation, the terminal ethanol concentration achieved at 41 and 57 g L −1 at solid loadings of 20% and 30% (w v −1 ), respectively. Washing with water enhanced the enzymatic hydrolysis and fermentation of FR. The terminal ethanol of furfural residue washed by 5 times water (WFR‐5) was 48 and 66 g L −1, higher than that from FR. The enhancement is mainly due to the removal of chemical inhibitors and increase of specific surface area. The scanning electron microscope (SEM) showed that FR contained fragmental structure, coarse surface and porous areas. Therefore, FR substrates represented good cellulase accessibility. It indicated that FR could be directly used for glucose and ethanol production without any further treatment. In addition, the quasi‐simultaneous enzymatic saccharification and combined fermentation (Q‐SSF) residues are characterized by fourier transform infrared spectroscopy (FTIR) and thermogravimetry (TG). Abstract : The raw furfural residue is used directly to enzymatic hydrolysis and fermentation without any treatment at a relative low cellulase loading. Washing with water enhances the glucose yield and ethanol production. With 5 times of water washing (WFR‐5), the glucose yield of WFR‐5 achieves at 96.9%. When using 30% (w v −1 ) of WFR‐5 fermentation, the ethanol concentration is 66 g L −1, with a total cellulose conversion of 92.6%.